Fourniers gangrene in modern conditions - Xudoyorov, Shakhzod; Mirkomilova, Mohinur; Burxonov, Utkir; Sayfieva, Gulshoda; Sheralieva, Nilufar; Daminov, Abdurasul Takhirovich (Science and Education, 2024)
Fournier’s gangrene (FG), or fulminant gangrene of the external genitalia, perineum and perianal region, is a rare, life-threatening urosurgical pathology. Currently, HF is considered as a variant of necrotizing fasciitis caused by a synergistic polymicrobial infection. A rapidly developing infectious process in the fascia causes thrombosis of the subcutaneous vessels and leads to gangrene of the overlying skin [1;2;7]. Despite its rarity, the disease has been known since ancient times.